Optimization of thermoplastic material for plastic injection molding process by using Taguchi method - Ashaari, Faleq Fitri; M. Amin, Sri Yulis (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Plastic injection molding process can produce a large amount of plastic components but can create several formations of defects such as sink marks and warpage. The objectives of this project are to minimize the defects of the final product of the plastic injection molding by optimizing the processing parameters and to compare the formation of defects between two different thermoplastic material which are polyethylene and polycarbonate. Taguchi method with L9 orthogonal array has been used to optimize the processing parameters which are mold temperature, melt temperature, injection pressure, and clamp open time to minimize the defects on both materials by running the simulation on Autodesk Moldflow Adviser software. The results show that the formation of defects can be minimized which is up to 36.2% after optimizing the processing parameters. Up to 76.49% formation of defects can be reduced by using different combination of processing parameters on different materials. Therefore, the new materials and processing parameters can be applied for further study to determine the behavior of the defects on the plastic components.